2022
DOI: 10.1016/j.jsxm.2022.01.518
|View full text |Cite
|
Sign up to set email alerts
|

Penile Prosthesis Placement by a Dedicated Transgender Surgery Unit: A Retrospective Analysis of Complications

Abstract: Background Penile prostheses may be used as a component of genital gender affirmation surgery for the purpose of achieving penile rigidity after phalloplasty, and transgender individuals experience higher complication rates than cisgender individuals. Aim To observe complications with transmasculine penile prosthesis surgery over time and across surgical conditions. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…There is substantial interest in alternatives to internal erectile prostheses for individuals who have undergone phalloplasty and are interested in using the neophallus for sexual penetration. 4 This reflects, in part, the fact that current internal devices have high failure rates and may require multiple surgeries for implantation and removal, 10,20,21 as well as pose a risk of causing damage to the neophallus. 22,23 As phalloplasty is, inherently, a complex surgery with a high risk of complications, 24 the idea of undergoing additional surgeries to attain sufficient rigidity for penetration may be untenable for some individuals.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial interest in alternatives to internal erectile prostheses for individuals who have undergone phalloplasty and are interested in using the neophallus for sexual penetration. 4 This reflects, in part, the fact that current internal devices have high failure rates and may require multiple surgeries for implantation and removal, 10,20,21 as well as pose a risk of causing damage to the neophallus. 22,23 As phalloplasty is, inherently, a complex surgery with a high risk of complications, 24 the idea of undergoing additional surgeries to attain sufficient rigidity for penetration may be untenable for some individuals.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred and eighty-five articles were identified using the search strategy above, and 15 studies [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] were included for analysis following abstract and full-text screening (Figure 1). Fourteen studies were retrospective and one study was prospective in nature.…”
Section: Quantity Of Evidence Identifiedmentioning
confidence: 99%
“…The most used flap for phalloplasty was the radial artery forearm free flap (RFFF), with only one study reporting the insertion of IPP following musculocutaneous latissimus dorsi free flap phalloplasty. 13 Five studies 6,7,12,13,17 reported outcomes on both IPP and malleable implants so only data relevant to IPP insertion were extracted and synthesised.…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%
See 2 more Smart Citations